2014
DOI: 10.1016/j.jneuroling.2014.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Language recovery and evidence of residual deficits after nonthalamic subcortical stroke: A 1 year follow-up study

Abstract: a b s t r a c tA variety of language disturbances including aphasia have been described after subcortical stroke but less is known about the factors that influence the long-term recovery of stroke-induced language dysfunction. We prospectively examined the role of the affected hemisphere and the lesion site in the occurrence and recovery of language deficits in nonthalamic subcortical stroke. Forty patients with unilateral basal ganglia stroke underwent language assessment within 1 week, 3 months and 1 year af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 70 publications
(76 reference statements)
0
1
0
Order By: Relevance
“…In contrast, language deficits can be recovered when cortical perfusion is regained ( Vallar et al, 1988 ). Even in the chronic stage of subcortical stroke, patients might have language deficits that relate to persistent cortical HP ( Peñaloza et al, 2014 ). However, a recent study has showed that cortical HP was not observed in most patients with left thalamic infarction and aphasia ( Sebastian et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, language deficits can be recovered when cortical perfusion is regained ( Vallar et al, 1988 ). Even in the chronic stage of subcortical stroke, patients might have language deficits that relate to persistent cortical HP ( Peñaloza et al, 2014 ). However, a recent study has showed that cortical HP was not observed in most patients with left thalamic infarction and aphasia ( Sebastian et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%